2014
DOI: 10.3889/oamjms.2014.007
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Interaction between Hepatitis C Virus Infection and Pulmonary Disorders: Assessment of Interferon Gamma and Alpha-1-Antitrypsin

Abstract: Objectives: To study lung diseases in chronic HCV infection and vice versa and to find immunological and/or hereditary interrelating factors. Material and Methods:Study included 134 individuals, all were subjected to screening for anti-HCV antibodies by ELISA, HCV-RNA by real time PCR, pulmonary function tests, quantitative assay of interferon gamma and alpha-1-antitrypsin in serum by ELISA and genotyping of alpha-1-antitrypsin gene by Light Cycler PCR.Results: 76.5% of chronic HCV patients had abnormal PFT (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…Another important finding in this study was that the spirometric parameters, FEV1 and FVC, were significantly lower in high-viremicand low-viremic groups compared to thenon-viremic group. These findings suggested that a high viremia level is associated with reduced lung functions in patients with CHC, and are consistent with those of Ezzeldin et al who reported an association between the presence of CHC infection and decline in lung functions and also stated that treatment of the CHC infection may improve pulmonary functions 15. Similarly, a 6- year follow up study, which confirmed this finding in asthmatic patients with CHC infection, showed that the annual decline in DLCO was higher in IFN non-responders than IFN responders 4.…”
Section: Discussionsupporting
confidence: 90%
“…Another important finding in this study was that the spirometric parameters, FEV1 and FVC, were significantly lower in high-viremicand low-viremic groups compared to thenon-viremic group. These findings suggested that a high viremia level is associated with reduced lung functions in patients with CHC, and are consistent with those of Ezzeldin et al who reported an association between the presence of CHC infection and decline in lung functions and also stated that treatment of the CHC infection may improve pulmonary functions 15. Similarly, a 6- year follow up study, which confirmed this finding in asthmatic patients with CHC infection, showed that the annual decline in DLCO was higher in IFN non-responders than IFN responders 4.…”
Section: Discussionsupporting
confidence: 90%